steilbergauf wrote:

If m≠0 and \(m-\frac{1+2m^2}{2m} = \frac{y}{m}\), then y is...?

Can someone please solve this question? I started by multiplying 2m, which didnt lead me anywhere!

Hi,

Please put the answer options as well.Coming back to the question we have

\(m - 1+2m^2/ 2m\)= y/m

So we get (2m^2 -1 -2m^2)/2m = y/m

or y =-1/2

What is the answer ??

_________________

“If you can't fly then run, if you can't run then walk, if you can't walk then crawl, but whatever you do you have to keep moving forward.”